Subspecies and Distribution. M.p.pennsylvanicusOrd,1815—extremeSEQuebecandNewBrunswick,Canada,andfromSouthDakota,N&ENebraska,andextremeNEKansasEtotheAtlanticcoastfromMaineStoSouthCarolina,USA. M.p.acadicusBangs,1897—PrinceEdwardIandNovaScotia,Canada. M.p.admiraltiaeHeller,1909—AdmiraltyI,Alaska,USA. M.p.alcorniBaker,1951—fromSWAlaska,USA,EtoSYukon,Canada. M.p.aphorodemusPreble,1902—SENunavutandNEManitoba,Canada. M.p.axtecusJ.A.Allen,1893—restrictedrangeinNWNewMexico,USA. ... - Wilson, Don E.; Mittermeier, Russell A.; Thomas E. Lacher, Jr (Zenodo, 2017)
Subspecies and Distribution. M.p.pennsylvanicusOrd,1815—extremeSEQuebecandNewBrunswick,Canada,andfromSouthDakota,N&ENebraska,andextremeNEKansasEtotheAtlanticcoastfromMaineStoSouthCarolina,USA. M.p.acadicusBangs,1897—PrinceEdwardIandNovaScotia,Canada. M.p.admiraltiaeHeller,1909—AdmiraltyI,Alaska,USA. M.p.alcorniBaker,1951—fromSWAlaska,USA,EtoSYukon,Canada. M.p.aphorodemusPreble,1902—SENunavutandNEManitoba,Canada. M.p.axtecusJ.A.Allen,1893—restrictedrangeinNWNewMexico,USA. M.p.chihuahuensisBradley&Cockrum,1968—knownonlyfromthevicinityofGaleana,NWChihuahua,Mexico. M.p.copelandiYoungman,1967—extremeSNewBrunswick,Canada. M.p.drummondiiAudubon&Bachman,1854—fromNAlaskaandNWYukonSEtoWOntario,Canada,andextremeWWashington,NIdaho,extremeNWMontana,NorthDakota,andextremeNSouthDakota,USA. M.p.enixusBangs,1896—C&NEQuebecandLabrador,Canada. M.p.finitusS.Anderson,1956—SWNebraska,extremeNEColorado,andextremeNWKansas,USA. M.p.fontigenusBangs,1896—WOntarioandSQuebec,Canada. ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 342, DOI: 10.5281/zenodo.6707142 ...